Tigecycline-induced acute pancreatitis with electrocardiogram changes in renal insufficiency elderly - Hong Chin Wee; Ru Shing Ng; Loke Meng Ong (European Journal of Case Reports in Internal Medicine)
Background: The prevalence of multidrug-resistant and extensively drug-resistant pathogens has led to increased reliance on broad-spectrum antimicrobials, such as tigecycline. This medicine is commonly used to treat complicated skin and intraabdominal infections as well as community-acquired pneumonia. However, the increasing use of tigecycline has been linked to serious complications, including acute pancreatitis. Case description: We present a case of tigecycline-induced acute pancreatitis in a 78-year-old man with complex medical conditions, including type 2 diabetes mellitus, chronic renal insufficiency, and triple vessel disease. The patient was initially treated with tigecycline for bilateral dry gangrene of his toes. Six days after initiation of the tigecycline treatment, the patient developed symptoms of acute pancreatitis with electrocardiogram changes. Magnetic resonance imaging confirmed the diagnosis of acute pancreatitis. Tigecycline was stopped promptly, and supportive treatment was initiated. The patient recovered from the acute pancreatitis and was discharged home. He later passed away at home due to his underlying cardiac disease. Conclusions: This case highlights the potential complications of tigecycline therapy, particularly in patients with significant comorbidities.